2020
DOI: 10.3897/italianbotanist.10.60022
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional IUCN Red List Assessments: 10

Abstract: In this contribution, the conservation status assessment of two vascular plants according to IUCN categories and criteria is presented. It includes the regional assessment of Jasione orbiculata Griseb. ex Velen. for Italy and of Vachellia gerrardii (Benth.) P.J.H.Hurter subsp. negevensis (Zohary) Ragup., Seigler, Ebinger & Maslin for Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…In this study, the same populations previously reported [37,38] are confirmed albeit with a substantial reduction in the population size. The observed causes of this reduction, at least in the last few years, are mainly attributable to human-related activities, while the effects of climate change are harder to quantify in these ecological contexts.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, the same populations previously reported [37,38] are confirmed albeit with a substantial reduction in the population size. The observed causes of this reduction, at least in the last few years, are mainly attributable to human-related activities, while the effects of climate change are harder to quantify in these ecological contexts.…”
Section: Discussionsupporting
confidence: 90%
“…The annual average of minimum temperature is increasing faster than maximum temperature and the overall temperature in Iraq is found to increase much faster compared to the global average [48]. Although precipitation is generally very low, the region receives transitory violent rainstorms in winter, which result in the uprooting of some trees [37,38]. These ecological conditions to which the plant is subjected could be particularly limiting for in situ germination and seedling survival [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations